Ecologia de Psitacídeos em um mosaico de ecossistemas urbanos e áreas naturais remanescentes em São Carlos, SP - Leoni, Ariane Maria (Universidade Federal de São Carlos, 2022)
Psitacines are typical representatives of tropical regions, with typically frugivorous and granivorous eating habits. Despite the large number of parrots in some degree of threat, some species of this group are common in urban areas, being tolerant to anthropic disturbances and flexible in terms of their eating habits. However, the study of the diet of these species in an urban environment is still incipient, with large gaps on how this aspect of the life history can influence their occupation and performance in cities. The objective of this thesis was to study the ecology of psitacines in urban areas and forest remnants in southeastern Brazil, focusing on trophic relationships. 36 points distributed in the municipality of São Carlos, SP, were sampled on a fortnightly basis, recording the species of birds and plants they consumed, as well as the number of individuals in each interaction, between September and March 2019-2020 and 2020 -2021. Four species of birds (Brotogeris chiriri – Yellow-chevroned Parakeet, Psittacara leucophthalmus – White-eyed Parakeet, Forpus xanthopterygius – Blue-winged Parrotlet and Eupsittula aurea – Peach-fronted Parakeet) were detected consuming food resources of 46 plant species. Considering the first two psittacine species, which accounted for 90% of the records, the consumption of native and exotic vegetable species occurred in all months throughout the study. Psittacara leucophthalmus equally consumes food resources of native and exotic vegetable species. However, the importance of exotic vegetable species was even greater for B. chiriri, which consumes them more than native ones, mainly in the first months of the studied period. In general, the data indicate that the studied species are highly plastic in terms of their eating habits, and that the consumption of vegetable exotic species may be important for the successful establishment of these populations in an urban environment.
Ecology of Psitacines in a mosaic of urban ecosystems and remaining natural areas in São Carlos, SP
Ecología de Loros en un mosaico de ecosistemas urbanos y áreas naturales remanentes en São Carlos, SP
Keywords: Plantas exóticas; Plasticidade alimentar; Redes de interação; Variação temporal; Alimentação de psitacídeos; Exotic plants; Food plasticity; Interaction networks; Temporal variation; Feeding psittacines; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS; CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL